The Practicing of Reverse Logistics in China's Electronic Products Manufacturing Industry - Chen, Xiaoming (2009)
Reverse logistics contains a series of activities including remanufacturing, reclaim, recycle, reconditioning , reuse etc. which enable the practitioners to recapture the residual value of returns. Thus, plenty of companies regard reverse logistics as a strategy not only for the purposes to save material consumption by reusing them, but also to reduce their negative influences on society and environment. As a serious problem in China, e-wastes have already damaged the people’s daily life. Some measures are encouraged by government that the electronic products manufacturers have obligation to dispose their electronic returns. This research is aimed to have a empirical investigation on the practicing of Chinese reverse logistics in the electronic products manufacturing industry. A depth interview is utilized to acquire the primary information about Chinese reverse logistics. The findings of this research is that the discarded electronic products could not be remanufactured sufficiently. The system of Chinese reverse logistics may become more efficient if closing the loop by taking back the cores that have been flowed into the irregular channel. The primary difficulties are analyzed in the discussion section as well as a return policy is designed for collecting the cores from rural villages.